2013
DOI: 10.1074/jbc.r113.472274
|View full text |Cite
|
Sign up to set email alerts
|

Programmed Heterogeneity: Epigenetic Mechanisms in Bacteria

Abstract: Contrary to the traditional view that bacterial populations are clonal, single-cell analysis reveals that phenotypic heterogeneity is common in bacteria. Formation of distinct bacterial lineages appears to be frequent during adaptation to harsh environments, including the colonization of animals by bacterial pathogens. Formation of bacterial subpopulations is often controlled by epigenetic mechanisms that generate inheritable phenotypic diversity without altering the DNA sequence. Such mechanisms are diverse, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
192
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 214 publications
(199 citation statements)
references
References 101 publications
4
192
0
3
Order By: Relevance
“…In contrast, Lobner-Olesen et al (55) and RobbinsMenke et al (56) found that the regulatory regions of differentially expressed genes were not enriched with GATC for both Dam Ϫ and Dam-overproducing mutants. While there are clear cases where methylation directly regulates gene expression in E. coli (57), the last two studies suggest that most differential gene expression in Dam mutants results from indirect effects of variable Dam concentrations on cell physiology, not from direct regulation of expression via methylation. Similarly, Ͼ30% of genes in E. coli C227-11 were differentially expressed after deleting the RM.EcoGIII methyltransferase, yet there were no clear connections to RM.EcoGIII methylation sites for most of these genes (22).…”
Section: Dynamics Of Dna Methylation and Gene Expressionmentioning
confidence: 99%
“…In contrast, Lobner-Olesen et al (55) and RobbinsMenke et al (56) found that the regulatory regions of differentially expressed genes were not enriched with GATC for both Dam Ϫ and Dam-overproducing mutants. While there are clear cases where methylation directly regulates gene expression in E. coli (57), the last two studies suggest that most differential gene expression in Dam mutants results from indirect effects of variable Dam concentrations on cell physiology, not from direct regulation of expression via methylation. Similarly, Ͼ30% of genes in E. coli C227-11 were differentially expressed after deleting the RM.EcoGIII methyltransferase, yet there were no clear connections to RM.EcoGIII methylation sites for most of these genes (22).…”
Section: Dynamics Of Dna Methylation and Gene Expressionmentioning
confidence: 99%
“…DNA MTases are ubiquitous enzymes in the prokaryotic world, where they play important roles in several cellular processes, such as host protection and epigenetic regulation (56)(57)(58). The genomes of various lytic and lysogenic phages have been shown to encode multi-and monospecific orphan MTases, which are not associated with any restriction enzymes.…”
Section: Fig 4 Comparison Of Restriction Patterns Of Dammentioning
confidence: 99%
“…Additionally, higher bacterial diversity in deep compared to shallow water corals 88,89 suggests that some deep habitat-specific microbes may be involved in nutrient cycling specific to the low-irradiance environments. Both genetic and epigenetic processes contribute to high phenotypic plasticity and rapid evolution in bacteria 90 . In addition, bacterial pathogens and mutualists are known to induce alterations in host epigenomes, leading to potentially long-lasting imprinting effects that provide a form of plasticity to their hosts 91 .…”
Section: Potential Involvement Of Microbes In Coral Acclimatizationmentioning
confidence: 99%